(untitled) (Journal of the College of Basic Education, 2022)
Bullying is a phenomenon that was and still is a major problem facing schools of all levels, primary ones in particular, and this phenomenon has many causes and manifestations that are multiple, complex and overlapping with each other. Explicit theorizing in the field of indicative psychological concepts.